Energy Management, Sustainability, and Ethics: An Islamic Perspective - Mohammad Khalil Elahee (International Institute of Islamic Thought, 2014)
The challenge of global climate change requires a radical change in our understanding of environmental issues, for its causes are linked to our dominant development model and its impact is significant at the grassroots level. Addressing energy production and consumption remains at the heart of any feasible solution. In this article, I define energy management (EM) as a systemic and systematic endeavor to optimize energy use through engineering and management tools in order to achieve political, economic, and environmental objectives. I also discuss what underpins EM’s ethical dimension, focusing on sustainability, and critically analyze the Islamic perspective to elaborate a value-based, universally acceptable, realistically applicable, and objective environmental ethic. By using EM as a vehicle toward sustainability, hence addressing climate change, I evaluate the outcomes of such a radical change in our understanding of environmental issues. I conclude by investigating whether a difference in vision with regard to faith and the hereafter can hinder a common engagement. Evidence is also sought from relevant specialist studies by non-Muslims, in which such Islamic principles as ordering the good and prohibiting the evil, ijmā‘, istiḥsān, istiṣḥāb, or istiṣlāḥhave been implemented to a given extent in all but name.